Nitrogen-induced surface area and conductivity modulation of carbon nanohorn and its function as an efficient metal-free oxygen reduction electrocatalyst for anion-exchange membrane fuel cells - Unni, SreeKuttan M.; Bhange, Siddheshwar N.; Illathvalappil, Rajith; Mutneja, Nisha; Patil, Kasinath R.; Kurungot, Sreekumar (SMALL, 2015)
Nitrogen-doped carbon morphologies have been proven to be better alternatives to Pt in polymer-electrolyte membrane (PEM) fuel cells. However, efficient modulation of the active sites by the simultaneous escalation of the porosity and nitrogen doping, without affecting the intrinsic electrical conductivity, still remains to be solved. Here, a simple strategy is reported to solve this issue by treating single-walled carbon nanohorn (SWCNH) with urea at 800 degrees C. The resulting nitrogen-doped carbon nanohorn shows a high surface area of 1836 m(2) g(-1) along with an increased electron conductivity, which are the pre-requisites of an electro catalyst. The nitrogen-doped nanohorn annealed at 800 degrees C (N-800) also shows a high oxygen reduction activity (ORR). Because of the high weight percentage of pyridinic nitrogen coordination in N-800, the present catalyst shows a clear 4-electron reduction pathway at only 50 mV overpotential and 16 mV negative shift in the half-wave potential for ORR compared to Pt/C along with a high fuel selectivity and electrochemical stability. More importantly, a membrane electrode assembly (MEA) based on N-800 provides a maximum power density of 30 mW cm(-2) under anion-exchange membrane fuel cell (AEMFC) testing conditions. Thus, with its remarkable set of physical and electrochemical properties, this material has the potential to perform as an efficient Pt-free electrode for AEMFCs.